Disseminated adenovirus infection after autologous stem cell transplant. Issue 1 (7th January 2020) - Kim, Nicole J.; Hyun, Teresa S.; Pergam, Steven A.; Issaka, Rachel B.
Abstract: Adenovirus is an infrequent but challenging viral complication of transplantation that is rarely reported after autologous stem cell transplant. We present a case of disseminated adenovirus infection in a woman who received an autologous stem cell transplant for treatment of multiple sclerosis. After presenting with post‐transplant episodic diarrhea and viremia, endoscopic biopsies and immunohistochemical staining confirmed the diagnosis of disseminated adenovirus infection. Her symptoms and viremia resolved after treatment with cidofovir. This case demonstrates that a high index of suspicion, a systematic clinical approach, and immunohistochemical tissue staining are necessary to diagnose disseminated adenovirus infection in an unexpected host.